Equity evaluation of intensive care unit admission based on comorbidity in hospitalized patients with COVID-19: a cross-sectional analysis - Zhu, Yang-Jie; Wang, Jia-Yue; Wu, Chen-Nan; Yu, Bo-Yang; Liu, Tong-Tong; Liu, Yuan; Zhang, Lu-Lu (Frontiers in Public Health, 2024)
Background Intensive care unit (ICU) beds played a crucial role in reducing mortality rates of patients with severe COVID-19. The surge in the number of patients led to a shortage of ICU beds, which may have exacerbated inequity of healthcare utilization. However, most attention has been focused on the horizontal equity in healthcare utilization, where individuals with the same needs receive the same services. Vertical equity, where individuals with higher needs receive more healthcare is often neglected, which might overestimate the equity. This study analyzes the vertical equity of ICU utilization among hospitalized patients with COVID-19. Methods In total, 18,547 hospitalized patients with COVID-19 in Maryland in 2020 were enrolled in this cross-sectional study. Logistic regression analysis was conducted to determine the independent factors affecting ICU utilization, and the Shapley value decomposition approach was implemented to assess the contribution of the independent variables to disparities in ICU admission. A concentration curve and concentration index were used to assess the vertical equity in healthcare utilization. Results ICU utilization by patients with COVID-19 was significantly affected by Charlson Comorbidity Index (CCI), with odds ratios (OR) 1.09 [95% confidence intervals (CI): 1.07–1.10; p < 0.001] in univariable analysis and 1.11 (95% CI: 1.09–1.13; p < 0.001) in multivariable regression analysis. The most important contributors were household income (32.27%) and the CCI (22.89%) in the Shapley value decomposition analysis. The concentration curve was below the line of equity, and the concentration index was 0.094 (95% CI: 0.076–0.111; p < 0.001), indicating that ICU utilization was concentrated among patients with a high CCI. These results were robust for all subgroup analyses. Conclusion Among 18,547 hospitalized patients with COVID-19 in Maryland in 2020, ICU utilization was significantly affected by comorbid conditions. The concentration curve and concentration index also indicated that ICU utilization was more concentrated in patients with a higher CCI. The results was consistent with the principle of vertical equity, whereby healthcare resources are more concentrated on COVID-19 patients with higher health needs.